The Effect of Earning Power, Company Size, Leverage, Capital Structure, and Liquidity on Company Value with Profit Growth as a Moderating Variable in Manufacturing Companies Listed on the Indonesia Stock Exchange in 2019-2021 - Madinah Madinah*; Atwal Arifin (Universitas Syiah Kuala, 2023)
Firm value is a study conducted by investors to assess the success and performance of the company which is reflected through the stock price in the market. This study aims to analyze the effect of earning power, company size, leverage, capital structure, and liquidity on company value with profit growth as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. The sampling technique used in this research is purposive sampling. Companies that meet the criteria in this study are 80 companies. This research uses analytical methods, namely multiple linear regression analysis and moderated regression analysis. The result of this study are that earning power, capital structure, and leverage. Meanwhile, firm size and leverage affect firm value, and pforit growth can moderate earning power and liquidity.